Pasolini al cinema: una mitologia della realtà - de Lange, Giulia (Status Quaestionis, 2025)
A reconstruction of the relations between Pier Paolo Pasolini and cinema, considering the chronological convergence with the first approach to Greek drama, aimed at illustrating and explaining the poet-neoregist’s point of view towards the new filmic medium. In particular, the ‘mythical’ definition of reality filmed in the films acts as a guiding thread of the analysis, which, starting from a re-reading of Pasolinian cinema theory, arrives at the three films on myth: Edipo re (1967), Medea (1969), Appunti per un’Orestiade africana (1970). These are three works that more than the whole of Pasolini’s filmography represent the director’s ideology, as well as being three adaptations that explicitly mark the passage, the same one experienced by Pasolini in those years, from literature to cinema.